Una conceptuación de la organización espacial doméstica: morfología y dinámica - Adánez Pavón, Jesús (Revista Española de Antropología Americana, 2003)
This paper starts from a defense of theory building in anthropology, and proposes a model to frame interpretations of domestic space organization. The model conceptualizes dwellings’ interior differentiation as a representation of social identities of and relations among its inhabitants and visitors; it brings together the morphological elements through which such dimensions are shaped in plan and points out the senses of their dynamics.